The Effectiveness of Picture and Picture Model and Synectic Model in Poetry Writing Study for 10th Grade of Senior High School Students - Muayah, Bindarin; Nuryatin, Agus; Wagiran, Wagiran (Universitas Negeri Semarang, 2023)
This research aims to find out the effectiveness of picture and picture model and synectic model in poetry writing study for 10th grade of Senior High School students. The populations for this research are the 10th grade Math and Science students of MA Assalafiyah and the 10th grade Math and Science students of SMA Negeri 1 Wanasari. The samples of this research are the first experiment group of 10th grade Math and Science students of MA Assalafiyah using picture and picture model and the second experiment group of 10th grade Math and Science students of SMA Negeri 1 Wanasari using synectic model. This research uses experimental research by applying factorial design. The result of this research shows that synectic model is more effective compared with the picture and picture model in poetry writing study for 10th grade of Senior High School students.